Overcoming Passion for Race in Malaysia Cultural Studies - Lim, David C. L. (Brill, 2008)
Overcoming Passion examines the passion for race in contemporary Malaysia. Broadly the essays look at the disjunction between the falsity of race as a scientific category and the entrenched belief that race determines one's rightful identity. They probe the ways in which individual minds and institutions of power fail or refuse to recognise and act in accordance with the knowledge that race exists only insofar as its existence is sustained by the believer's belief in it. The contributors draw from a burgeoning but under-examined archive of Malaysia-related social texts, ranging from … read moremedia and technological discourse, popular culture and literary production to historical writings, produced originally in English, Malay and Mandarin Chinese.